A quantitative version of the Hopf–Oleinik lemma for a quasilinear non-uniformly elliptic operator - Moreira, Diego; Santos, Jefferson Abrantes; Soares, Sergio H. Monari (Annales Fennici Mathematici, 2024)
This paper establishes a quantitative version of the Hopf–Oleinik lemma (HOL) for a quasilinear non-uniformly elliptic operator of the form \(L_∞ u: =2Δ_∞ u+Δ u\). One key point in the proof is the passage from non-uniformly elliptic operators to locally uniformly ones via a new, uniform, and, rescaled version of the gradient estimate obtained by Evans and Smart for solutions to a family of non-uniformly quasilinear elliptic operators.